UJI AKTIVITAS ANTIBAKTERI ISOLAT ACTINOMYCETES DARI TANAH PEKARANGAN TERHADAP Escherichia coli DAN Bacillus subtilis - -, Ambarwati -; -, Retno Sintowati; -, Sri Darnoto (STIKES Muhammadiyah Klaten, 2009)
ABSTRACT : Soil is one of microorganism habitat, included actinomycetes. In the same habitat, there are several symbiosises between microorganism, one of them is antagonism. Antagonism can make a lucky for human life, because it can produce antibiotic, included antibacteria. Now, some research is focussed to actinomycetes that is indicated as the biggest antibiotic producer. The aims of the research were : 1) to know the quantity of actinomycetes isolate from the garden land and 20 to knew the potentially of actinomycetes isolate to inhibit the growth of E.coli and B. subtilis. From this research was found 25 isolates actinomycetes from garden land sample. Based on colour grouping result there were 9 colour group. Based on the result of inhibition test to test bacteria, it was known that from the 9 isolates, 8 isolates could inhibit the grouwth of test bacteria : 6 isolates (75%) could inhibit B. Subtilis (gram positif bacteria) and 2 isolates could inhibit B. Subtilis (gram positif bacteria) and E.coli (gram negative bacteria). Based on the research it can be concluded thata actinomycetes can be isolated from garden land and potentially as antibacteria producer. Â Key words : actinomycete, garden land, antibacteria